Positive electrode material and preparation method and application thereof

By using lithium oxides and lithium salts as composite lithium sources, the alkalinity of the surface of high-nickel positive electrode materials is reduced, the gelation problem is solved, and the slurry stability and electrochemical performance of lithium-ion batteries are improved.

CN119160948APending Publication Date: 2024-12-20WUXI LINGYI FUTURE RES INST OF NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310734944.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

During the sintering process, high-nickel positive electrode material produces excessive lithium OH and reacts with air to form alkaline substances, resulting in an increase in residual alkali on the surface of the material, causing the binder to gel, lose its fluidity, and affecting the processing and electrochemistry of lithium-ion batteries. performance.

Method used

The lithium oxide and lithium salt are used as composite lithium sources to reduce the content of lithium hydroxide and lithium carbonate on the surface of the material, and the material purity and slurry stability are improved through dry mixing and high-temperature sintering, thereby reducing the possibility of gel formation.

Benefits of technology

It effectively improves the slurry stability of the positive electrode material, reduces the risk of gas production of batteries, and improves electrochemical performance and convenience of processing and manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160948A_ABST
    Figure CN119160948A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a positive electrode material precursor and a composite lithium source, and calcining to obtain the positive electrode material, wherein the composite lithium source comprises lithium oxide and lithium salt. The lithium oxide and the lithium salt are used as the composite lithium source, the lithium oxide can provide a main lithium source for the reaction process and ensure the purity of the synthesized material, the lithium salt can improve the mixing condition in the reaction process, and the combination of the lithium oxide and the lithium salt can effectively promote the proceeding of reaction kinetics and reduce the content of lithium hydroxide and lithium carbonate on the surface of the material; therefore, the total amount of residual alkali on the surface of the material is reduced, the slurry stability of the material is effectively improved, and the positive electrode slurry with gelling resistance is more beneficial to processing and manufacturing of a battery. Meanwhile, the low alkalinity of the positive electrode material can reduce the risk of gas production of the battery and improve the electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] One of the major challenges faced by high-nickel cathode materials in lithium-ion batteries during the manufacturing process is the gelation phenomenon when mixing with binders and solvents to prepare slurry, which causes the slurry to lose fluidity and cannot be coated on the collector. The deterioration of slurry fluidity is caused by the side reaction between the alkaline substances in the cathode material and the binder.

[0003] At present, most of the high-nickel positive electrode materials are prepared using LiOH as the lithium source. For example, CN110854370A discloses a method for preparing a high-nickel nickel cobalt manganese oxide positive electrode material: 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH·H2O are used as raw materials, and A (including Zr, Mg, Ti or Nb, etc.) elements are doped and mixed uniformly; the mixed material is sintered once; Al2O3, TiO2 or Na2TiO3 is added to the primary sintered material, and Al2O3, TiO2 or Na2TiO3-coated positive electrode material LiNi is obtained by secondary sintering. 0.83- x Co 0.11 Mn 0.06 A x O2, x=0.001-0.002. CN109888235A discloses a graded high-nickel ternary positive electrode material and its preparation method and application. The graded high-nickel ternary positive electrode material is prepared by the following method: 1) mixing a high-nickel polycrystalline precursor, anhydrous LiOH and a doping additive, sintering, and then mixing the obtained product with a coating additive and sintering to obtain a high-nickel polycrystalline material; 2) mixing a ternary single crystal precursor, a lithium source and a doping additive, sintering, and then mixing the obtained product with a coating additive and sintering to obtain a ternary single crystal material; 3) mixing a high-nickel polycrystalline material and a ternary single crystal material, or mixing the mixture with a coating additive and then sintering. CN109192966A discloses a high-nickel ternary positive electrode material for lithium-ion batteries and its preparation method. The preparation method includes preparing a high-nickel material LiNi by a hydroxide co-precipitation method. 0.8 Co 0.1 Mn 0.1 O2, and the surface was coated with AlF3 high nickel material LiNi 0.8 Co 0.1 Mn 0.1 O2, to obtain high nickel ternary positive electrode material

[0004] However, when high-nickel cathode materials are sintered, lithium is in excess. Therefore, the excess LiOH after sintering and the free lithium on the surface of the high-nickel cathode material will react with CO2 and H2O in the air to form LiOH and Li2CO3 on the surface of the material, resulting in an increase in residual alkali on the surface of the high-nickel cathode material. In addition, in the high-nickel cathode material slurry, a large amount of alkali on the surface of the high-nickel cathode material will cause the binder PVDF to undergo an elimination reaction, remove HF, and the generated double bonds will cause cross-linking reactions between PVDF molecular chains to form a gel. At the same time, the solvent will catalyze hydrolysis in the presence of alkaline substances to produce substances such as dimethylamine. The alkalinity of this type of organic amine is higher than that of lithium hydroxide, lithium carbonate, etc., and it is more destructive to PVDF.

[0005] Therefore, providing a method for preparing a positive electrode material that is resistant to gelation is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a positive electrode material and a preparation method and application thereof. The present invention uses lithium oxide and lithium salt as a composite lithium source. Lithium oxide can provide the main lithium source for the reaction process to ensure the purity of the synthesized material. Lithium salt can improve the mixing condition during the reaction. The combination of the two can effectively promote the reaction kinetics, reduce the content of lithium hydroxide and lithium carbonate on the surface of the material, thereby reducing the total amount of residual alkali on the surface of the material, reducing the possibility of gelation, and effectively improving the slurry stability of the material. The positive electrode slurry with gelation resistance is more conducive to the processing and manufacturing of the battery. At the same time, the low alkalinity of the positive electrode material can also reduce the risk of battery gas production and improve the electrochemical performance of the battery.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a positive electrode material, the preparation method comprising:

[0009] Mixing a positive electrode material precursor and a composite lithium source, and calcining to obtain the positive electrode material;

[0010] Wherein, the composite lithium source includes lithium oxide and lithium salt.

[0011] The present invention uses lithium oxide and lithium salt as composite lithium sources. Lithium oxide can provide the main lithium source for the reaction process to ensure the purity of the synthesized material. Lithium salt can improve the mixing condition during the reaction process. The combination of the two can effectively promote the reaction kinetics, reduce the content of lithium hydroxide and lithium carbonate on the surface of the material, and then reduce the total amount of residual alkali on the surface of the material, reduce the possibility of gelation, improve the slurry stability of the material, and the positive electrode slurry with gelation resistance is more conducive to the processing and manufacturing of the battery. At the same time, the low alkalinity of the positive electrode material can also reduce the risk of battery gas production and improve the electrochemical performance of the battery.

[0012] In the present invention, if lithium hydroxide is used as a lithium source and mixed with a positive electrode material precursor for sintering, lithium hydroxide will remain on the surface of the prepared positive electrode material. The presence of hydroxide will increase the alkalinity of the material, making it easier to promote a cross-linking reaction between polymer molecular chains of the binder to form a gel, thereby destroying the stability of the slurry. In addition, lithium hydroxide will react with carbon dioxide in the air to generate lithium carbonate. The presence of carbonate will increase the risk of gas production in the battery and reduce the electrochemical performance of the battery.

[0013] It should be noted that the stability of the slurry refers to the anti-agglomeration and anti-precipitation properties, and the slurry does not produce stratification when placed for a long time. The method for evaluating the stability of the slurry in the present invention is to test the degree of change of the viscosity of the slurry over time during the static process.

[0014] Preferably, based on the mass of the composite lithium source as 100%, the mass fraction ratio of the lithium oxide to the lithium salt is (80%-95%):(5%-20%), wherein the selection range of the lithium oxide is 80%-95%, for example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, etc., and the selection range of the lithium salt is 5%-20%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc.

[0015] In the present invention, if the mass fraction ratio of lithium oxide to lithium salt is too small, that is, the lithium oxide content is small, the synthesized material purity is low and the performance is poor; if the mass fraction ratio of lithium oxide to lithium salt is too large, that is, the lithium oxide content is large, the reaction is difficult and the kinetics is poor.

[0016] Preferably, the lithium oxide includes lithium oxide and / or lithium peroxide.

[0017] Preferably, the lithium salt includes any one of lithium nitrate, lithium chloride, lithium sulfate, lithium acetate, lithium oxalate or lithium fluoride, or a combination of at least two thereof.

[0018] Preferably, the composite lithium source is a mixture of lithium oxide and lithium acetate.

[0019] In the present invention, a mixture of lithium oxide and lithium acetate is used as a composite lithium source. The low-melting-point lithium acetate will be preferentially decomposed during the sintering process, which can improve the diffusivity of the lithium salt. In combination with lithium oxide, it can fully react with the precursor and improve the purity of the product.

[0020] Preferably, the cathode material precursor is a high nickel oxide and / or a high nickel hydroxide, and the molar content of nickel in the high nickel oxide and the high nickel hydroxide is greater than 60%, for example, 65%, 70%, 75% or 80%, etc. Wherein, taking the total metal content in the high nickel oxide and / or the high nickel hydroxide as 100%, the molar content of nickel is greater than 60%.

[0021] Preferably, the chemical formula of the high nickel oxide is Ni x Co y M 1-x-y O2, 0.7≤x≤1, 0≤y≤0.15, M element includes Al and / or Mn.

[0022] Preferably, the chemical formula of the high nickel hydroxide is Ni x Co y M 1-x-y (OH)2, 0.7≤x≤1, 0≤y≤0.15, M element includes Al and / or Mn. Wherein, based on the total molar content of Ni, Co and Mn being 100%, the molar content of Ni accounts for greater than or equal to 70% and less than or equal to 100%.

[0023] Preferably, the mixing method is dry mixing.

[0024] Preferably, the specific steps of mixing include:

[0025] The lithium oxide and the lithium salt are premixed to obtain the composite lithium source, and then the composite lithium source is mixed with the positive electrode material precursor. Premixing refers to the premixing of lithium oxide and lithium salt, which is to mix the composite lithium source evenly to ensure that the lithium can play a role; mixing refers to the mixing of the composite lithium source and the positive electrode material precursor to ensure a more complete reaction to improve the purity of the product.

[0026] Preferably, the mixing time is 0.5-5 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0027] Preferably, the oxygen content in the calcination atmosphere is greater than or equal to 90%, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%.

[0028] Preferably, the calcination temperature is 650-900°C, for example, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C.

[0029] In the present invention, if the calcination temperature is too low, the reaction is incomplete, the crystallization performance of the material is poor, and an amorphous structure is easily generated, which affects the electrochemical properties of the material; if the calcination temperature is too high, the grains of the material become larger and the specific surface area becomes smaller, which is not conducive to the release and embedding of lithium ions in the material.

[0030] Preferably, the calcination time is 6-30 h, for example, 6 h, 9 h, 12 h, 15 h, 18 h, 21 h, 24 h, 27 h or 30 h, etc., preferably 12-24 h.

[0031] Preferably, the calcination is followed by crushing and screening.

[0032] As a preferred technical solution, the preparation method comprises the following steps:

[0033] (1) premixing lithium oxide and lithium salt to obtain a composite lithium source;

[0034] (2) dry-mixing the composite lithium source and the cathode material precursor for 0.5-5 hours to obtain a mixture;

[0035] (3) In an atmosphere with an oxygen content of 90% or more, calcining the mixture at 650-900° C. for 6-30 hours, crushing and sieving, to obtain the positive electrode material.

[0036] The dry mixing device can be any device with a mixing function known in the art. Specifically, the dry mixing device includes any one of a mortar, a ball mill, a mixer, a fusion machine, a high-speed stirring mill, a tube mill, a cone mill, a rod mill or a sand mill.

[0037] In a second aspect, the present invention provides a positive electrode material, which is prepared by the preparation method described in the first aspect.

[0038] Preferably, the chemical formula of the positive electrode material is Li a Ni x Co y M 1-x-y O2, 0.95≤a≤1.1, 0.7≤x≤1, 0≤y≤0.15, M element includes Al and / or Mn.

[0039] Among them, 0.95≤a≤1.1, for example, it can be 0.95, 0.97, 0.99, 1.01, 1.03, 1.05, 1.07, 1.09 or 1.1, etc.

[0040] Among them, 0.7≤x≤1, for example, it can be 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1, etc.

[0041] Among them, 0≤y≤0.15, for example, it can be 0, 0.03, 0.06, 0.09, 0.12 or 0.15.

[0042] In a third aspect, the present invention provides a positive electrode slurry, wherein the positive electrode slurry comprises the positive electrode material as described in the second aspect.

[0043] In a fourth aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode slurry as described in the third aspect.

[0044] In a fifth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the fourth aspect.

[0045] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention uses lithium oxide and lithium salt as a composite lithium source, so that the surface residue of the prepared positive electrode material is lithium oxide, thereby reducing the total amount of residual alkali on the surface of the material, reducing the possibility of gelation, and effectively improving the slurry stability of the material. The positive electrode slurry with gelation resistance is more conducive to the processing and manufacturing of the battery. At the same time, the low alkalinity of the positive electrode material also reduces the risk of battery gas production and improves the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the XRD spectrum of the positive electrode material provided in Example 1 of the present invention.

[0049] Figure 2 This is the viscosity change curve of the positive electrode slurry provided in Application Example 5 of the present invention. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0051] The raw materials involved in the following specific embodiments of the present invention are all commercially available products.

[0052] Example 1

[0053] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0054] (1) 0.8 Co0.1 Mn 0.1 )O, lithium oxide and lithium nitrate are dry mixed for 2.5 hours to obtain a mixture;

[0055] Wherein, the mass fraction ratio of lithium oxide to lithium nitrate is 90%:10%;

[0056] (2) In an atmosphere with an oxygen content of 95%, the mixed material was calcined at 750° C. for 20 h, crushed and sieved to obtain the positive electrode material, whose chemical formula is Li(Ni 0.8 Co 0.1 Mn 0.1 )O2.

[0057] Figure 1 The XRD spectrum of the positive electrode material provided in Example 1 shows that the product is pure phase Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, where I(003) / I(104)=1.6, indicating that the degree of lithium-nickel mixing is low.

[0058] Example 2

[0059] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0060] (1) 0.85 Co 0.05 Mn 0.1 )(OH)2, lithium oxide and lithium chloride are dry mixed for 0.5h to obtain a mixture;

[0061] Wherein, the mass fraction ratio of lithium oxide to lithium chloride is 80%:20%;

[0062] (2) In an atmosphere with an oxygen content of 90%, the mixed material was calcined at 650° C. for 30 h, crushed and sieved to obtain the positive electrode material, whose chemical formula is Li(Ni 0.85 Co 0.05 Mn 0.1 )O2.

[0063] Example 3

[0064] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:

[0065] (1) 0.83 Co 0.05 Mn 0.12 )O, lithium oxide and lithium sulfate are dry mixed for 5 hours to obtain a mixture;

[0066] Wherein, the mass fraction ratio of lithium oxide to lithium sulfate is 95%:5%;

[0067] (2) In an atmosphere with an oxygen content of 100%, the mixed material was calcined at 900° C. for 6 h, crushed and sieved to obtain the positive electrode material, whose chemical formula is Li(Ni 0.83 Co 0.05 Mn 0.12 )O2.

[0068] Example 4

[0069] The difference between this embodiment and embodiment 1 is that lithium oxide and lithium nitrate are pre-mixed, and the obtained composite lithium source is then mixed with (Ni 0.8 Co 0.1 Mn 0.1 )O mixed.

[0070] The rest of the preparation methods and parameters were the same as those in Example 1.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that lithium nitrate is replaced by lithium acetate.

[0073] The rest of the preparation methods and parameters were the same as those in Example 1.

[0074] Example 6

[0075] The difference between this embodiment and embodiment 1 is that lithium oxide is replaced by lithium peroxide.

[0076] The rest of the preparation methods and parameters were the same as those in Example 1.

[0077] Example 7

[0078] The difference between this embodiment and embodiment 1 is that the mass fraction ratio of the lithium oxide and the lithium nitrate in step (1) is 75%:25%.

[0079] The rest of the preparation methods and parameters were the same as those in Example 1.

[0080] Example 8

[0081] The difference between this embodiment and embodiment 1 is that the mass fraction ratio of the lithium oxide to the lithium nitrate in step (1) is 98%:2%.

[0082] The rest of the preparation methods and parameters were the same as those in Example 1.

[0083] Example 9

[0084] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (1) is 600°C.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Example 10

[0087] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (1) is 950°C.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 1 is that lithium oxide and lithium nitrate are replaced by lithium hydroxide.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 1 is that only lithium oxide is added, and lithium nitrate is not added.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 1 is that only lithium nitrate is added, and lithium oxide is not added.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Application Example 1

[0099] This application example provides a method for preparing a positive electrode slurry, and the preparation method comprises the following steps:

[0100] (1) 0.45 g of polyvinylidene fluoride, 0.3 g of conductive carbon black and 1 g of N-methylpyrrolidone were mixed at 1500 rpm for 3 min to obtain a mixed solution;

[0101] (2) The mixed solution was mixed with 29.25 g of the positive electrode material provided in Example 1 and 4.4 g of N-methylpyrrolidone at 1500 rpm for 3 min to obtain a positive electrode slurry;

[0102] The mass fraction ratio of the positive electrode material, conductive carbon black and polyvinylidene fluoride provided in Example 1 is 97.5%:1%:1.5%.

[0103] Application Example 2

[0104] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 2.

[0105] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0106] Application Example 3

[0107] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 3.

[0108] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0109] Application Example 4

[0110] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 4.

[0111] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0112] Application Example 5

[0113] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 5.

[0114] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0115] Figure 2 The viscosity change curve of the positive electrode slurry provided in Application Example 5 is shown. It can be seen from the curve that the viscosity can be maintained at <6000cps after being left standing for more than 10 hours in an environment with a humidity of 20%, indicating that it has good fluidity and resistance to gelation.

[0116] Application Example 6

[0117] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 6.

[0118] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0119] Application Example 7

[0120] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 7.

[0121] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0122] Application Example 8

[0123] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 8.

[0124] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0125] Application Example 9

[0126] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 9.

[0127] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0128] Application Example 10

[0129] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by Example 10.

[0130] The rest of the preparation methods and parameters were the same as those in Application Example 1.

[0131] Application Comparative Example 1

[0132] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by comparative example 1.

[0133] The rest of the preparation methods and parameters were the same as those in Comparative Example 1.

[0134] Application Comparative Example 2

[0135] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by comparative example 2.

[0136] The rest of the preparation methods and parameters were the same as those in Comparative Example 1.

[0137] Application Comparative Example 3

[0138] The difference between this application example and application example 1 is that the positive electrode material in this application example is provided by comparative example 3.

[0139] The rest of the preparation methods and parameters were the same as those in Comparative Example 1.

[0140] Performance Testing

[0141] (i) The positive electrode slurries provided in Application Examples 1-10 and Comparative Application Examples 1-3 were left to stand in an environment with a humidity of 20% for more than 10 hours, and a viscometer was used to perform a slurry stability test.

[0142] The test results are shown in Table 1.

[0143] (II) The positive electrode materials, conductive carbon black and binder polyvinylidene fluoride provided in Examples 1-10 and Comparative Examples 1-3 were prepared into a 60% solid content N-methylpyrrolidone solution in a mass ratio of 85:5:10, stirred evenly to obtain a positive electrode slurry, evenly coated on an aluminum foil, dried at 120°C for 10 hours under vacuum, and punched into a 10 mm diameter disc as a positive electrode sheet. The positive electrode sheet, the negative electrode sheet (metal lithium sheet with a diameter of 16 mm), the diaphragm (Celgard 2400 microporous polypropylene membrane) and the electrolyte (1 mol / L LiPF6 / EC+DMC in a volume ratio of 1:1) were assembled into a CR2032 button cell in an argon glove box for electrochemical performance testing.

[0144] The test conditions are: maintain a constant temperature of 25°C, a voltage range of 3.0-4.3V, charge at a constant current and constant voltage of 0.05C, test the charge and discharge capacity of the CR2032 button battery, calculate the irreversible capacity (first charge capacity - first discharge capacity = irreversible capacity), and calculate the first coulombic efficiency.

[0145] The test results are shown in Table 2.

[0146] Table 1

[0147]

[0148]

[0149] The method for evaluating the stability of the slurry in the present invention is to test the degree of change of the viscosity of the slurry over time during the static state. Generally, the viscosity of the slurry remains consistent with the initial viscosity during the static state, indicating that the slurry has the best stability. If the viscosity changes during the static state, and the degree of viscosity change is smaller than that of the initial viscosity, it indicates that the slurry has better stability.

[0150] Table 1 Analysis:

[0151] It can be seen from the data results of Application Examples 1-3 that the present invention uses lithium oxide and lithium salt as composite lithium sources. Lithium oxide can provide the main lithium source for the reaction process to ensure the purity of the synthesized material, and lithium salt can improve the mixing conditions during the reaction. The combination of the two can effectively promote the reaction kinetics and improve the slurry stability of the material. The positive electrode slurry with resistance to gelation is more conducive to the processing and manufacturing of the battery.

[0152] From the comparison of the data results of Application Example 1 and Application Example 4, it can be seen that if lithium oxide and lithium nitrate are pre-mixed, and then the obtained composite lithium source is mixed with (Ni 0.8 Co 0.1 Mn 0.1 )O mixing, premixing the composite lithium source evenly to ensure that the lithium can play a role, which can effectively improve the slurry stability of the material.

[0153] By comparing the data results of Application Example 1 and Application Example 5, it can be seen that if lithium nitrate is replaced with lithium acetate, the low-melting-point lithium acetate will decompose preferentially during the sintering process, which can improve the diffusivity of the lithium salt. Combined with lithium oxide, it can fully react with the precursor, improve the purity of the product, and thus obtain a material with excellent slurry stability.

[0154] By comparing the data results of Application Example 1 and Application Example 6, it can be seen that if lithium oxide is replaced with lithium peroxide, the strong oxidizing lithium salt is more likely to promote the reaction between lithium and the high-nickel positive electrode material precursor, improve the purity, and reduce the generation of residual alkali on the surface, then the slurry stability of the material can be further improved.

[0155] By comparing the data results of Application Example 1 with those of Application Examples 7-8, it can be seen that if the mass fraction ratio of lithium oxide to lithium salt is too small, the purity of the synthesized material will be low and the stability will be poor; if the mass fraction ratio of lithium oxide to lithium salt is too large, the reaction will be difficult, the kinetics will be poor, and it will be difficult to obtain a material with excellent slurry stability.

[0156] By comparing the data results of Application Example 1 with Application Examples 9-10, it can be seen that if the calcination temperature is too low, the reaction is incomplete, the crystallization performance of the material is poor, and an amorphous structure is easily generated, affecting the slurry stability of the material; if the calcination temperature is too high, the grains of the material become larger and the specific surface area becomes smaller, which is not conducive to the release and embedding of lithium ions in the material, and the slurry stability of the material is poor.

[0157] By comparing the data results of Application Example 1 with those of Comparative Example 1, it can be seen that if lithium oxide and lithium nitrate are replaced with lithium hydroxide, lithium hydroxide will remain on the surface of the prepared positive electrode material. The presence of hydroxide will increase the alkalinity of the material and make it easier to promote cross-linking reactions between the polymer molecular chains of the binder to form a gel, thereby destroying the stability of the slurry.

[0158] From the comparison of the data results of Application Example 1 and Application Comparative Example 2, it can be seen that if only lithium oxide is used as the lithium source, the stability of the slurry is greatly weakened. From the comparison of the data results of Application Example 1 and Application Comparative Example 3, it can be seen that if only lithium nitrate is used as the lithium source, the stability of the slurry is greatly weakened. This shows that the single lithium source lacks the synergistic effect of the composite lithium source, resulting in insufficient reaction between lithium and the high-nickel positive electrode material precursor, increased surface residual alkali, and poor slurry stability of the material.

[0159] Table 2

[0160]

[0161]

[0162] Table 2 Analysis:

[0163] It can be seen from the data results of Examples 1-3 that the present invention uses lithium oxide and lithium salt as a composite lithium source. Lithium oxide can provide the main lithium source for the reaction process to ensure the purity of the synthesized material. Lithium salt can improve the mixing situation during the reaction. The combination of the two can effectively promote the reaction kinetics, reduce the content of lithium hydroxide and lithium carbonate on the surface of the material, and thus reduce the total amount of residual alkali on the surface of the material. The low alkalinity of the positive electrode material also reduces the risk of battery gas production and improves the electrochemical performance of the battery.

[0164] From the comparison of the data results of Example 1 and Example 4, it can be seen that if lithium oxide and lithium nitrate are mixed in advance, and then the obtained composite lithium source is mixed with (Ni 0.8 Co 0.1 Mn 0.1 )O mixed, the obtained material has more excellent electrochemical properties.

[0165] By comparing the data results of Example 1 and Example 5, it can be seen that if lithium nitrate is replaced by lithium acetate, the low-melting-point lithium acetate will be preferentially decomposed during the sintering process, which can improve the diffusivity of the lithium salt. Combined with lithium oxide, it can fully react with the precursor, improve the purity of the product, and thus obtain a positive electrode material with excellent electrochemical properties.

[0166] By comparing the data results of Example 1 and Example 6, it can be seen that if lithium oxide is replaced with lithium peroxide, the strong oxidizing lithium salt is more likely to promote the reaction between lithium and the high-nickel positive electrode material precursor, improve the purity, reduce the formation of residual alkali on the surface, and the slurry stability of the material can be further improved, then the charge and discharge specific capacity of the material can be further improved.

[0167] By comparing the data results of Example 1 with those of Examples 7-8, it can be seen that if the mass fraction ratio of lithium oxide to lithium salt is too small, the electrochemical performance of the synthesized positive electrode material is poor; if the mass fraction ratio of lithium oxide to lithium salt is too large, the reaction is difficult, the kinetics are poor, and it is difficult to effectively improve the electrochemical performance of the positive electrode material.

[0168] By comparing the data results of Example 1 with those of Examples 9-10, it can be seen that if the calcination temperature is too low, the reaction is incomplete, the crystallization performance of the material is poor, and an amorphous structure is easily generated, which affects the electrochemical properties of the material; if the calcination temperature is too high, the grains of the material become larger and the specific surface area becomes smaller, which is not conducive to the release and embedding of lithium ions in the material.

[0169] By comparing the data results of Example 1 with those of Comparative Example 1, it can be seen that if lithium oxide and lithium nitrate are replaced with lithium hydroxide, lithium hydroxide will remain on the surface of the prepared positive electrode material. The lithium hydroxide will react with carbon dioxide in the air to form lithium carbonate. The presence of carbonate will increase the risk of gas production in the battery and reduce the electrochemical performance of the battery.

[0170] From the comparison of the data results of Example 1 and Comparative Example 2, it can be seen that if only lithium oxide is used as the lithium source, the electrochemical performance of the material will be significantly deteriorated.

[0171] From the comparison of the data results of Example 1 and Comparative Example 3, it can be seen that if only lithium nitrate is used as the lithium source, the electrochemical performance of the material is significantly deteriorated. This shows that the single lithium source lacks the synergistic effect of the composite lithium source, resulting in insufficient reaction between lithium and the high-nickel positive electrode material precursor, increased surface residual alkali, poor slurry stability of the material, and significantly poor electrochemical performance of the material.

[0172] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises: Mixing a positive electrode material precursor and a composite lithium source, and calcining to obtain the positive electrode material; Wherein, the composite lithium source includes lithium oxide and lithium salt.

2. The preparation method according to claim 1, characterized in that: Taking the mass of the composite lithium source as 100%, the mass fraction ratio of the lithium oxide to the lithium salt is (80%-95%):(5%-20%); Preferably, the lithium oxide comprises lithium oxide and / or lithium peroxide; Preferably, the lithium salt includes any one of lithium nitrate, lithium chloride, lithium sulfate, lithium acetate, lithium oxalate or lithium fluoride, or a combination of at least two thereof; Preferably, the composite lithium source is a mixture of lithium oxide and lithium acetate.

3. The preparation method according to claim 1 or 2, characterized in that: The positive electrode material precursor is high-nickel oxide and / or high-nickel hydroxide, and the molar content of nickel in the high-nickel oxide and the high-nickel hydroxide is greater than 60%.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mixing method is dry mixing; Preferably, the specific steps of mixing include: Premixing the lithium oxide and the lithium salt to obtain the composite lithium source, and then mixing the composite lithium source with the positive electrode material precursor; Preferably, the mixing time is 0.5-5h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The oxygen content in the calcination atmosphere is greater than or equal to 90%; Preferably, the calcination temperature is 650-900°C; Preferably, the calcination time is 6-30h, preferably 12-24h; Preferably, the calcination is followed by crushing and screening.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) premixing lithium oxide and lithium salt to obtain a composite lithium source; (2) dry-mixing the composite lithium source and the cathode material precursor for 0.5-5 hours to obtain a mixture; (3) In an atmosphere with an oxygen content of 90% or more, calcining the mixture at 650-900° C. for 6-30 hours, crushing and sieving, to obtain the positive electrode material.

7. A positive electrode material, characterized in that: The positive electrode material is prepared by the preparation method according to any one of claims 1 to 5; Preferably, the chemical formula of the positive electrode material is Li a Ni x Co y M 1-x-y O2, 0.95≤a≤1.1, 0.7≤x≤1, 0≤y≤0.15, M element includes Al and / or Mn.

8. A positive electrode slurry, characterized in that: The positive electrode slurry includes the positive electrode material as claimed in claim 7.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode slurry as claimed in claim 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.